Access Node Dimensioning for IPTV Traffic Using Effective Bandwidth - Smiesko, Juraj; Uramova, Jana (Communications - Scientific letters of the University of Zilina, 2012)
This article presents a dimensioning of capacity of access node (Black Diamond 12 804R) for IPTV source (6 channels of IPTV), which was one part of our project with Slovak Telecom. We describe IPTV traffic by two mathematic models and use Effective bandwidth for dimensioning of required link capacity with respect to QoS.